AN INVESTIGATION OF PROFIT EFFICIENCY OF DRY SEASON VEGETABLE FARMING BUSINESS ALONG RIVER BENUE BANK IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Ivom, G.A.; Onah, A.E.; Maimusa, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the profit efficiency of dry season vegetable farming business along River Benue Bank in Makurdi Local Government Area of Benue State, Nigeria. The study described socioeconomic characteristics of the farmers and examined profit efficiency of dry season vegetable farming. Data were collected from 125 respondents that were selected using multistage sampling procedure. Descriptive and inferential statistics were used to analyse the data. The result showed that 64.80 % of the farmers were male with average age of 42.18 years and 84.00 % were married with average household size of about 7. Result of the Cobb-Douglas stochastic frontier profit model reveals an average profit efficiency of 0.49. The inefficiency model showed that age (-0.6509167) and education (-5.535188) have decreasing effects on profit inefficiency and household size (1.084588) has increasing effect on profit inefficiency. The study concludes the dry season vegetable farming profit efficiency is low and is significantly influenced by age, household size and level of education of the farmers. Also, dry season vegetable production in the study area is dominated by males who are still in their active age and married with household size that can supply family labour. The farmers can read and write. The study recommends that, there is need to encourage farmers to explore alternative marketing channels such as direct sales to consumers to increase profit margins; farmers should be advice to consider diversifying vegetable production to include high-value crops that can increase profitability; training and capacity building programmes should be provided to farmers through informal education using extension agents to improve production and marketing skills of the farmers; there is need to invest in infrastructure such as storage facilities and transportation networks to reduce spoilage and improve market access and policies such as provision of subsidies and credit facilities should be developed to support small-scale farmers.